REFORMA ADMINISTRAȚIEI PUBLICE ÎN PERSPECTIVA INTEGRĂRII REPUBLICII MOLDOVA ÎN UNIUNEA EUROPEANĂ - Zaporojan, Livia (CEP USM, 2024)
The provision of public services to citizens and economic agents can be made more efcient through the reform of the central and local public administration launched in 2014 at the time of the ratifcation of the association agreement with the European Union. The reform acquired particular importance after June 23, 2022, when the Republic of Moldova was granted the status of a candidate country. The reform is necessary both for the evolution of the state’s sustainability and for the realization of the commitments of integration into the European Union. The reform and broad cooperation of the central and local public authorities will be eﬀective through the implementation of the Public Administration Reform Strategy of the Republic of Moldova.
PUBLIC ADMINISTRATION REFORM IN THE PERSPECTIVE OF THE INTEGRATION OF THE REPUBLIC OF MOLDOVA IN THE EUROPEAN UNION
ZAPOROJAN, Livia. Reforma administrației publice în perspectiva integrării Republicii Moldova în Uniunea Europeană. In: Integrare prin cercetare și inovare: conferința științifică națională cu participare internațională. Ştiinţe sociale, 9-10 noiembrie 2023. CEP USM, 2024, pp. 201-208. ISBN 978-9975-62-688-0.
Keywords: public authority; public administration; central public authority